2021
DOI: 10.3390/su132313356
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Twitter Negativity Pre- vs. Mid-COVID-19 Pandemic: An LDA Application on London Public Transport System

Abstract: The coronavirus pandemic has affected everyday life to a significant degree. The transport sector is no exception, with mobility restrictions and social distancing affecting the operation of transport systems. This research attempts to examine the effect of the pandemic on the users of the public transport system of London through analyzing tweets before (2019) and during (2020) the outbreak. For the needs of the research, we initially assess the sentiment expressed by users using the SentiStrength tool. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Our findings on the significant increase in the number of negative tweets (P<001) during the pandemic is consistent with previously published literature [46]. Politis et al [47] showed an increase in negative sentiment on certain dates by analyzing tweets that were posted before and after the outbreak of the COVID-19 pandemic.…”
Section: Principal Findingssupporting
confidence: 92%
“…Our findings on the significant increase in the number of negative tweets (P<001) during the pandemic is consistent with previously published literature [46]. Politis et al [47] showed an increase in negative sentiment on certain dates by analyzing tweets that were posted before and after the outbreak of the COVID-19 pandemic.…”
Section: Principal Findingssupporting
confidence: 92%
“…The word cloud is a simple way to make an initial assessment of topics in flood tweets, its results have to be further analyzed, since single keywords cannot easily provide a clear sense of a topic (Politis et al, 2021). The following section describes the topic modeling results of the public perception in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Predominant keywords in a corpus of tweet tokens can indicate the top topics discussed by users (Politis et al, 2021). In this context, word frequency analysis was used to infer the number of important words in the corpus, which can be also used to identify event hotspots and their changing trends.…”
Section: Frequency Of Abstract Related To the Floodsmentioning
confidence: 99%
“…The class names may directly indicate how to deal with customers' satisfaction or dissatisfaction in relevant classes. To discover relevant topics, two approaches were applied-an expert interpretation of the content (bag of words where relevant keywords are defined in advance, followed by a supervised interpretation) and artificial intelligence-based unsupervised analysis (i.e., Latent Dirichlet Allocation LDA), where the data is first processed automatically, followed by an expert interpretation of the emerged topics [24].…”
Section: Semantic Analysismentioning
confidence: 99%